Pertumbuhan Cabai Merah (Capsicum annum L.) Varietas Lokal dengan Penerapan Paket Teknologi Produksi Lipat Ganda (Proliga) dan Teknologi Petani pada Fase Vegetatif - Sartika, Sartika; Maryuni, Ayu; Amelia, Kiki; Nieldalina, Nieldalina (JURNAL AGROPLASMA, 2024)
Red chili (Capsicum annuum L.) belongs to the Solanaceae plant family and is one of the important vegetable crops in Indonesia. The demand for red chilies is getting higher day by day and to meet consumer needs both in terms of quality and quantity, it is necessary to increase red chili production. One effort to increase production is by implementing Double Fold Production Technology (Proliga) for red chilies. Proliga Technology (Double Production) is a technology package whose aim is to double chili production. The aim of this experiment is to determine the growth of local varieties of red chili (Capsicum annum L.) by applying the double production technology package (Proliga) and farmer technology in the vegetative phase. The experiment was carried out from August to September 2020 at the BPTP (Agricultural Technology Assessment Center) Sukarami, Gunung Talang District, Solok Regency, West Sumatra. The experiment was carried out on 2 treatments, namely: A (Red chili plants using proliga technology), and B (Red chili plants using farmer technology). Each treatment consisted of 3 replications and each replication contained 5 experimental samples so that the total number of experiments was 30 samples of red chili plants. From the results of the experiments that have been carried out, it can be concluded that good growth of chili plants during the vegetative period can be seen from the number of shoots and number of leaves found in treatments using proliga technology (double production). Meanwhile, good growth of chili plants during the vegetative period can be seen from plant height in treatments using farmer technology. However, if observations are continued until 7 weeks after planting (WAP), it is estimated that good results will be obtained, namely proliga technology because based on data on the increase in height of chili plants using proliga technology at the age of 6 WAP, there has been a significant increase and has almost succeeded in catching up with the height of chili plants using farmer technology. with a difference of 0.3 cm. Keywords: red chili, proliga technology, vegetative